Brain & heart from computer science perspective - Taha Alshaikhli, Imad Fakhri (2014)
Computer science and biology have enjoyed a long and fruitful relationship for decades. However, these two dimensions are studied separately and rarely integrated. EEG and ECG have been very useful for capturing the signals of the brain and heart. In computer science, a prime challenge is to interpret these signals into meaningful data and to develop algorithms and applications to establish interface between humans’ bio-signal and computer. In this talk, I will present possible research areas in both combined fields in order to harvest the fruits of the integration between biology field and computer science field. Also, I will discuss the benefits of combining these fields with medicine. For example, early detection of children abnormal brain activities might help us deepen our understanding in their diagnosis. Therefore, there is a necessity to incorporate computer science with humans’ bio-signals.